Wilms' tumour 1‐associating protein inhibits endothelial cell angiogenesis by m6A‐dependent epigenetic silencing of desmoplakin in brain arteriovenous malformation. Issue 9 (13th April 2020) - Wang, Lin‐jian; Xue, Yimeng; Li, Hao; Huo, Ran; Yan, Zihan; Wang, Jie; Xu, Hongyuan; Wang, Jia; Cao, Yong; Zhao, Ji‐zong
Abstract: Brain arteriovenous malformations (AVMs) are congenital vascular abnormality in which arteries and veins connect directly without an intervening capillary bed. So far, the pathogenesis of brain AVMs remains unclear. Here, we found that Wilms' tumour 1‐associating protein (WTAP), which has been identified as a key subunit of the m6A methyltransferase complex, was down‐regulated in brain AVM lesions. Furthermore, the lack of WTAP could inhibit endothelial cell angiogenesis in vitro. In order to screen for downstream targets of WTAP, we performed RNA transcriptome sequencing (RNA‐seq) and Methylated RNA Immunoprecipitation Sequencing technology (MeRIP‐seq) using WTAP‐deficient and control endothelial cells. Finally, we determined that WTAP regulated Desmoplakin (DSP) expression through m6A modification, thereby affecting angiogenesis of endothelial cells. In addition, an increase in Wilms' tumour 1 (WT1) activity caused by WTAP deficiency resulted in substantial degradation of β‐catenin, which might also inhibit angiogenesis of endothelial cells. Collectively, our findings revealed the critical function of WTAP in angiogenesis and laid a solid foundation for the elucidation of the pathogenesis of brain AVMs.